Analysis and Optimization of the K-Means Algorithm in Determining Course Scheduling - M Martiano; Yoshida Sari; Farid Akbar (Journal of Information System Research (JOSH), 2023)
Preparation of course schedules is the core activity of learning and learning. This is felt by study programs, where assignments are arranged through lecturer assignments, to class determination and class schedule dissolution, therefore the right application is needed to be able to arrange schedules automatically, then by using the k-means method you can arrange schedules correctly , in designing this application requires a prototyping application development method which gives good results where the clusters formed reach 17 clusters where the course schedule is made with the results of the Means Sequence Error in cycle 1 which is 65.66% with an accuracy of 54.06%. so that it is continued in cycle 2 the MSE value is 87.55% with an accuracy of 84.03%. The K-Means algorithm can accurately determine course schedules in the faculties of computer science and information technology.